A longitudinal study of the use of high frequency nouns among Malaysian secondary school students / Zhang Xinxin - Zhang, Xinxin (2017)
This study investigates how second language development takes place over time. It takes nouns as a starting point, and explores how selected nouns are used differently in the texts taken from the Longitudinal Corpus of Languaculturer Narrative Texts (Chau, 2015). The texts (based on the same prompt) consist of four parts written at four different points in time by the same group of students. Five most frequent nouns river, girl, flowers, lake, and friend together with their respective singular or plural forms were selected for the investigation. Pattern Grammar (Hunston & Francis, 1999) was adopted to explore how these selected words were used over time. The findings show both a constructive process and a reductionist process (Chau, 2015) operate at the same time in learner data, and indicate that language development is a non-linear and complex process (e.g., Larsen-Freeman, 2006, 2009; Ortega, 2009; Ellis, 2011; Chau, 2015). Meanwhile, it is found that students are able to use more adjectives and nouns to modify the words in focus at a later period in time, which shows students’ lexical repertoire has expanded across time. Implications of the study are provided.